Characterization of the prevalence of HIV-infected patients aged 50 years and above in Tiantai County, Zhejiang Province from 2006 to 2020 - GE Junhua; HU Haiyan; PANG Tianlan; WANG Shanling; ZHU Guiwei (Shanghai yufang yixue)
ObjectiveTo analyze the epidemiological characteristics of the newly reported HIV-infected cases aged ≥50 years in Tiantai County from 2006 to 2020, and to provide a scientific basis for the formulation of intervention measures and control strategies for the elderly.MethodsData of the newly reported HIV-infected individuals aged ≥50 years in Tiantai County from 2006 to 2020 were analyzed. A trend χ2 test was used to analyze the changing trends of the composition ratio over the years.ResultsA total of 201 HIV-infected cases aged ≥50 years were newly reported from 2006 to 2020, accounting for 52.62% of the total reported cases, and the proportion of HIV- infected patients aged ≥50 years in the total number of reported cases increased from 12.50% in 2011 to 80.00% in 2020, showing a yearly increasing trend (χ2trend=36.898, P<0.001). The mean age of the elderly at diagnosis of HIV infection was (64.8±9.1) years old, and the average age of infection was (58.1±9.3) years old. Patients who were male (79.10%), married with a spouse (58.21%), with an educational level of primary school and below (68.16%), with a local registered residence (75.12%) and peasants (88.06%) were associated with increased risk of HIV infection. Heterosexual transmission (89.55%) was the major route of HIV transmission among the HIV-infected cases aged ≥50 years and 75.12% of them were detected while visited medical and healthcare facilities. Among heterosexual transmission, males were more likely to be infected through non-marital heterosexual contact(χ2=229.381, P<0.001), while females were more likely to be infected through contact with their positive spouse or fixed sexual partner(χ2=216.699, P<0.001). The AIDS epidemic had affected 15 townships (streets) in the county. Pingqiao Town and Chicheng Street were seriously affected, with the confirmed cases accounted for 45.27% of the total number of the cases in the county.ConclusionThe number of the newly reported HIV-infected cases aged ≥50 years in Tiantai County showed a rapid growth trend from 2006 to 2020. Males with low educational level predominated in the total number of the cases. Commercial heterosexual behavior is the main route of infection. Lack of timely detection and management on positive clandestine prostitutes, resulting in the existence of gathering trend in the key towns. Crackdown on clandestine prostitution should be strengthened, and interventions on high-risk sexual behaviors should be carried out, in order to promote the acquisition of HIV/AIDS prevention knowledge and behavioral change for the elderly, furthermore, to control the spread and epidemic of HIV/AIDS.